PLASMA JET FOR THE TREATMENT OF EYELID FLACIDITY - França Gomes Vieira, Bruna; Regina Veronezi, Lauscea; Vivianne Nogueira, Marcia; Rabelo Lima Barbosa, Chrystianne; Rodrigues Ribeiro, Henrique; Lemos Maia, Juliana; Elayne Silva Montezuma, Gina; Januzzi Santos, Marcelo (Health and Society, 2023)
The present descriptive observational study aimed to evaluate the clinical improvement, satisfaction and postoperative symptoms of a patient who underwent non-surgical plasma jet blepharoplasty. A patient underwent a plasma jet session in the upper and lower passages, photographic images were recorded at T0 (pre-procedure), T1 (immediate post-procedure) and T2 (up to 8 weeks post-procedure) to monitor clinical improvement. Postoperative symptoms and patient satisfaction were recorded through clinical monitoring in the first 7 days and questioning about satisfaction at 30, 60 and 90 days. A significant clinical improvement was observed, however the patient’s overall satisfaction can be affected by the relative delay in the formation of collagen fibers and the clear result appears only after a certain time, leaving the patient less willing to undergo the procedure again. Symptoms were mainly reported in the first week. The technique has shown promise as it is minimally invasive, low-cost with quick recovery and can be an alternative to the traditional surgical procedure, but more prospective clinical studies are needed to determine its efficacy and safety.